PENGARUH PENGETAHUAN PERPAJAKAN DAN PEMAHAMAN AKUNTANSI TERHADAP KEPATUHAN WAJIB PAJAK DENGAN KUALITAS PELAYANAN FISKUS SEBAGAI VARIABEL MODERASI - Neni Marlina Br Purba; Yuliadi Yuliadi; Erni Yanti Natalia; Poniman Poniman (LPPM Universitas Putera Batam, 2026)
The purpose of this study is to examine how tax knowledge and accounting understanding affect taxpayer compliance, with the quality of tax service as a moderating variable. This study was conducted quantitatively using a survey method targeting taxpayers registered at the Batam Selatan Tax Office. A simple random sampling method using the Slovin formula was employed, resulting in a sample of 100 respondents. With the assistance of SmartPLS, the Partial Least Squares Structural Equation Modeling (PLS-SEM) data analysis method was utilized. The results indicate that knowledge of taxation and accounting, as well as the quality of tax administration services, significantly influence taxpayer compliance. Conversely, knowledge of taxation significantly influences taxpayer compliance. Furthermore, the quality of tax service moderates the relationship between knowledge of taxation and taxpayer compliance but does not moderate the relationship between accounting understanding and taxpayer compliance. This study indicates that improving tax service and providing ethics-based tax training are crucial for enhancing taxpayer compliance.